2021
DOI: 10.1186/s12984-021-00816-4
|View full text |Cite
|
Sign up to set email alerts
|

Foot progression angle estimation using a single foot-worn inertial sensor

Abstract: Background The foot progression angle is an important measure used to help patients reduce their knee adduction moment. Current measurement systems are either lab-bounded or do not function in all environments (e.g., magnetically distorted). This work proposes a novel approach to estimate foot progression angle using a single foot-worn inertial sensor (accelerometer and gyroscope). Methods The approach uses a dynamic step frame that is recalculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Additionally, only a single short-term motor learning session was performed with a short washout time and thus further research is needed to explore long-term learning and FPA gait modification adoption as a new motor task [45]- [47]. Finally, it should be noted that FPA estimation in environments with magnetic distortion could be affected and that recent research has proposed new FPA algorithms that do not rely on magnetometer data [48], [49], which could allow for FPA training to be performed in environments that contain magnetic distortions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only a single short-term motor learning session was performed with a short washout time and thus further research is needed to explore long-term learning and FPA gait modification adoption as a new motor task [45]- [47]. Finally, it should be noted that FPA estimation in environments with magnetic distortion could be affected and that recent research has proposed new FPA algorithms that do not rely on magnetometer data [48], [49], which could allow for FPA training to be performed in environments that contain magnetic distortions.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference of 2.7 degrees between the systems was found when performing the gait modification strategies. A similar study found a comparable difference in FPA of 2.6 degrees between a foot-worn inertial sensor and a motion capture system [20]. It is unclear whether the location of the IMU in detecting deformation of the foot (when loading in extreme positions) could have caused a varus or valgus effect on the FPA.…”
Section: Validitymentioning
confidence: 93%
“…Gait retraining to achieve this has been successful 76 , but feedback is required for an individual to sustain new walking styles. Wouda et al 77 used a single foot-worn IMU and a dedicated algorithm to calculate walking direction and real-time Foot Progression Angle (FPA). In a study by Xia et al 78 , the FPA sensor was built into the sole of the shoe, and together with a haptic device (vibrator), they showed that participants could control FPA very precisely (within 3 ) on a treadmill.…”
Section: Wearablesmentioning
confidence: 99%